Shopping motivations of Paylater users - Ghina Amalia Syifani; Martina Dwi Mustika (Australian Journal of Psychology)
Objective Despite Paylater’s increasing popularity in Indonesia, no research potentially has explored the influence of Paylater users’ shopping motivation on purchase intention. This topic is important to research to create a healthier shopping environment for marketers and users. This paper presents two studies addressing this gap.Method Study 1 explored the values of shopping motivation influencing purchase intention in Indonesia using a non-experimental method with 299 participants aged from 18 to 40 years in Indonesia. Study 2 used experimental vignette methods to strengthen the first study’s results. This study involved 752 participants with the same characteristics as Study 1.Results The results of Study 1 show that both utilitarian and hedonic motivations influence Paylater users’ purchase intention in Indonesia, and all shopping motivation values positively influence utilitarian and hedonic motivations. In Study 2, we found that values of convenience, customisation, adventure/exploration and gratification affect the purchase intention of Paylater users in Indonesia.Conclusion The results demonstrate both motivations influence purchase intention, but hedonic has the most significant influence, and all shopping motivation values are significant. Therefore, each value can motivate Indonesian Paylater users’ intention to purchase.Key Points What is known about this topic: